"We do what we can do to save a woman" health workers' perceptions of health facility readiness for management of postpartum haemorrhage. Issue 1 (31st December 2020) - Alwy Al-beity, Fadhlun; Pembe, Andrea B.; Kwezi, Hilda A.; Massawe, Siriel N.; Hanson, Claudia; Baker, Ulrika
ABSTRACT: Background : In many low-resource settings, in-service training is a common strategy to improve the performance of health workers and ultimately reduce the persistent burden of maternal mortality and morbidities. An evaluation of the Helping Mothers Survive Bleeding After Birth (HMS BAB) training as a single-component intervention in Tanzania found some positive albeit limited effect on clinical management and reduction of postpartum haemorrhage (PPH). Aim : In order to better understand these findings, and particularly the contribution of contextual factors on the observed effects, we explored health workers' perceptions of their health facilities' readiness to provide PPH care. Methods : We conducted 7 focus group discussions (FGDs) and 12 in-depth interviews (IDIs) in purposively selected intervention districts in the HMS BAB trial. FGDs and IDIs were audio-recorded, transcribed and translated verbatim. Thematic analysis, using both inductive and deductive approaches, was applied with the help of MAXQDA software. Results : Health workers perceive that their facilities have a low readiness to provide PPH care, leading to stressful situations and suboptimal clinical management. They describe inconsistencies in essential supplies, fluctuating availability of blood for transfusion, and ineffective referral system. In addition, there are challenges in collaboration, communication and leadership support, which is perceived to prevent effective management of cases within the facility as well as in referral situations. Health workers strive to provide life-saving care to women with PPH despite the perceived challenges. In some health facilities, health workers perceive supportive clinical leadership as motivating in providing good care. Conclusion : The potential positive effects of single-component interventions such as HMS BAB training on clinical outcome may be constraint by poor health facility readiness, including communication, leadership and referral processes that need to be addressed.